Adaptability and stability of performance of field bean varieties and varietal mixtures in the Zona da Mata area, state of Minas Gerais - Pessanha, Gilberto Gastim; Vieira, Clibas; Silva, Corival Candido da; Cardoso, Antonio Américo; Silva, José Carlos; Sediyama, Carlos S. (Pesquisa Agropecuaria Brasileira, 2014)
This study included the bean (Phaseolus vulgaris L.) varieties 'Ricopardo 896', 'Ricobaio 1014’, 'Costa Rica 1031', 'Manteigão Fosco 11', 'Manteigão 977', ‘Jalo', and two mixtures of these varieties, 896+1014+1031 and 11 +977+Jalo, which consisted of equal proportions of each component. These were tested in eight environments in the Zona da Mata area, state of Minas Gerais. No significant difference in yield was found among the mixtures and their components, but it appears that blending of varieties can have some yield advantage. 'Ricopardo 896' and ‘Costa Rica 1031' were the most responsive varieties to environmental improvement; 'Ricobaio 1014' and 'Manteigão 977' were the least responsive. The mixtures and the other varieties remained at an intermediate position. 'Ricobaio 1014 was the only treatment that showed stability of performance in the various environments. 'Ricobaio 1014' was generally the dominant component in a mixture, while in the other mixture the dominant was 'Manteigão 977' or 'Jalo'.The same study, repeated in eight simulated environments (4 levels of fertilization x 2 planting seasons) at Viçosa, in the same area, gave results somewhat different.